Enciclopedia Limbilor Romanice. - Montes Giraldo, José Joaquín (Thesavrvs, 2022)
Reseña de libros. Mioara Avram, Jana Balacciu-Matei, Alexandra Cunitja, I. Fischer, Christian Ionescu, Coman Lupu, Sebastiana Popescu-Fischer, Sanda Reinheimer Ripeanu, Marius Sala, Oana Sálistcanu-Cristca, Ion Toma, Mariana Tutescu, Laura Vasiliu, Ioana Vintilá-Rádulescu.